Incidence and prevalence of hepatitis c virus infection among persons who inject drugs in New York City: 2006–2013. (1st July 2015) - Jordan, Ashly E.; Des Jarlais, Don C.; Arasteh, Kamyar; McKnight, Courtney; Nash, Denis; Perlman, David C.
Highlights: We examine changes in estimated hepatitis c virus (HCV) incidence and prevalence among drug users in NYC. The estimated HCV incidence among people who inject drugs remains high. HCV prevalence among people who inject drugs remains high. Combined HCV prevention including treatment for people who inject drugs is needed. Abstract: Background: Hepatitis C virus infection is a source of significant preventable morbidity and mortality among persons who inject drugs (PWID). We sought to assess trends in hepatitis C virus (HCV) infection among PWID from 2006 to 2013 in New York City (NYC). Methods: Annual cross-sectional surveys of PWID entering a large drug abuse treatment program were performed. Risk behavior questionnaires were administered, and HIV and HCV testing were conducted. Comparisons were made with prior prevalence and incidence estimates in 1990–1991 and 2000–2001 reflecting different periods of combined prevention and treatment efforts. Results: HCV prevalence among PWID ( N : 1535) was 67% (95% CI: 66–70%) during the study period, and was not significantly different from that observed in 2000–2001. The estimated HCV incidence among new injectors (persons injecting for ≤6 years) during 2006–2013 was 19.5/100 PYO (95% CI: 17–23) and did not differ from that observed in 2000–2001 (18/100 PYO, 95% CI: 14–23/100). Conclusions: Despite the expansion of combined prevention programming between 2000–2001 and 2006–2013, HCV prevalence remained high. Estimated HCV incidence among new injectors also remained high, and not significantly lower than in 2000–2001, indicating that expanded combined prevention efforts are needed to control the HCV epidemic among PWID in NYC.